Cost of human papillomavirus vaccine delivery at district and health facility levels in Zimbabwe: A school-based vaccination program targeting multiple cohorts. (31st March 2022) - Hidle, Anna; Brennan, Timothy; Garon, Julie; An, Qian; Loharikar, Anagha; Marembo, Joan; Manangazira, Portia; Mejia, Nelly; Abimbola, Taiwo
Abstract: Background: After a pilot project in 2014–15 Zimbabwe introduced the human papillomavirus (HPV) vaccine nationally in 2018 for girls aged 10–14 years through a primarily school-based vaccination campaign with two doses administered at 12-month intervals. In 2019, a first dose was delivered to a new cohort of girls in grade 5 of girls age 10 years if out-of-school (OOS), along with a second dose to the 2018 multiple cohorts. Additional effort was made to identify and mobilize OOS girls by Village Health Workers (VHWs) in the community. Zimbabwe reported 1, 569, 905 doses of HPV vaccine administered during the 2018 and 2019 campaigns. This analysis evaluated the cost of Zimbabwe's national HPV vaccine introduction. Methods: A retrospective, incremental, ingredients-based cost analysis from the provider perspective was conducted in 2018 and 2019. Financial and economic cost data were collected at district and health facility levels using a two-stage cluster sampling approach and four cost dimensions: program activity, resource input, payer, and administrative level. Costs are presented in 2020 US$ in total and per dose. Results: The total weighted costs for combined district and health facility administrative levels were US$ 828, 731 (financial) and US$ 2, 060, 943 (economic). For service delivery, the total weighted cost per dose was US$ 0.16 (financial) and US$ 0.59 (economic). The program activities with the largest share of total weighted financial cost were training (37% of total) and service delivery (30%), while the largest shares of total weighted economic costs were service delivery (45%) and training (19%). Efforts by VHWs to reach OOS girls resulted in an additional US$ 2.99 in financial cost per dose and US$ 7.79 in economic cost per dose. Conclusion: The service delivery cost per dose was lower than that documented in the pilot program cost analysis in Zimbabwe and studies elsewhere, reflecting a campaign delivery approach that spread fixed costs over a large vaccination cohort. The additional cost of reaching OOS girls with the HPV vaccine was documented for the first time in low- and middle-income countries, which may provide information on potential costs for other countries.